TREND KEPUTUSAN BELANJA ONLINE MAHASISWA FAKULTAS EKONOMI FE UM ANGKATAN 2014 - Inggarani Ulfa Yovirizka; Wahjoedi Wahjoedi (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
The development of increasingly sophisticated technology has brought changes to Indonesian. People try to fulfill and adjust their life with technology changes, one of them is internet. Internet technology makes consumers easy to purchase a product by online shopping. According to APJII research in 2016, online shop is a frequently visited content and university students are the largest access. That is why the researcher wants to know Economics Students year 2014 online shopping trends decision. This research is aimed to: (1) to know economics students online shopping trend decision, (2) to know economics students online shopping decision,(3) to know online shopping problems. This study uses a qualitative method with the kind of phenomenology and uses snowball sampling technique. The data was collected by doing observe, interview, and documentation. The data sources are economics student year 2014. The result of the research shows: (1) the high intensity of student spending reaches twice until five times in a month, (2) easy, practical, save time and effort, price and product variety and ease of payment and delivery. (3) the problem is the goods received are not in accordance with the image, the duration of the seller's response, and the slow delivery of goods. The advice given after conducting this research is Student should be careful when they are online shopping, especially to resolve deception.DOI: https://dx.doi.org/10.17977/UM014v11i12018p041